2003
DOI: 10.1046/j.1365-8711.2003.06423.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral response of the pulsationally induced shocks in the atmosphere of BW Vulpeculae

Abstract: BW Vulpeculae (BW Vul) is remarkable for exciting an extremely strong radial pulsation mode which grows through its outer envelope and forms visible shock features in the atmosphere. Material propelled upwards by the shock returns violently to the lower photosphere where it creates a second shock just before the start of the next cycle. We have obtained three nights of echelle data for this star over about five pulsation cycles (P= 0.201 d) in 2000 September in order to investigate the effects of atmospheric s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…This is similar to what is observed in the magnetic stars, implying that the same low-velocity part of the stellar wind is affected, even though different mechanisms are involved. This phenomenon, where the low-velocity part of the stellar wind is influenced by strong pulsations has previously been observed in strong pulsators, such as BW Vul (Burger et al 1982;Smith & Jeffery 2003).…”
Section: Uv Variabilitysupporting
confidence: 52%
See 1 more Smart Citation
“…This is similar to what is observed in the magnetic stars, implying that the same low-velocity part of the stellar wind is affected, even though different mechanisms are involved. This phenomenon, where the low-velocity part of the stellar wind is influenced by strong pulsations has previously been observed in strong pulsators, such as BW Vul (Burger et al 1982;Smith & Jeffery 2003).…”
Section: Uv Variabilitysupporting
confidence: 52%
“…DJ found that the asymmetry of this triplet, as measured from data of van Hoof (1961), could only partly be explained by the quadratic effects of rotation (see, e.g., Saio 1981) and suggested that a strong magnetic dipole field of the order of 5-10 kG could explain this discrepancy. In a more recent analysis (Paper I) the asymmetry was found to be a factor of 2 smaller than before, and Pamyatnykh et al (2004) could entirely account for the asymmetry in terms of quadratic rotational effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is a radial pulsator, whose amplitude is the largest known in the Galaxy. The shock waves have been proved to propagate through its atmosphere (Smith & Jeffery 2003). MWC 342 can fall into the range of β Cephei variable according to the errorbars of derived stellar parameters.…”
Section: Vii) Mass Transfer Binarymentioning
confidence: 99%
“…For instance, Young et al (1981) suggest that a stationary layer is generated during the infalling atmospheric motion by the strong increase in temperature and gas pressure, and that the line doubling is not the result of the propagation of a shock front. Smith & Jeffery (2003) use thermodynamical considerations, especially temperature variations, to explain the Van Hoof effect, since no phase-lag is detected between the different optical lines they considered. In MGFC we were able to measure a phase-lag between the Si  and Hα variations which was interpreted in terms of the presence of progressive waves (Mathias & Gillet 1993).…”
Section: Introductionmentioning
confidence: 99%